Impact of compensatory growth on survival in newborn kittens - Mugnier, Amélie; Gaillard, Virginie; Chastant, Sylvie (Frontiers in Veterinary Science, 2024)
In the feline species, the mortality of live-born kittens over the first 2 months of life is around 10%. Although some losses are inevitable, progress in veterinary medicine and improved knowledge of feline neonatalogy should make it possible to reduce them to a lower level. The objectives of this study were: (i) to describe early growth in kittens, and (ii) to assess whether low birth weight kittens develop compensatory growth during the first week of life and if so, whether compensatory growth is associated with increased chances of survival. Using data collected from 5,504 kittens born in 193 different French catteries, five growth rates were calculated to reflect the growth of kittens during the first week after birth. Low birth weight kittens had higher growth rates than normal birth weight kittens. In addition, low birth weight kittens whose early growth was in the lowest 25% had a significantly higher 0–2 months mortality rate than all the other groups. Weight loss (or lack of weight gain) between birth and Day 2 was identified as a risk factor for 0–2 months mortality whatever the birth weight category. Finally, critical early growth thresholds were determined separately for low and normal birth weight kittens. These figures could help caregivers to validate the adequacy or inadequacy of kitten early growth. They will be able to quickly identify and provide appropriate care for the kittens whose growth is deemed insufficient in order to improve their chances of survival.